Optimasi Keterampilan Menyimak Bahasa Arab Dengan Media Youtube - Eka Lutfiyatun (Sekolah Tinggi Ilmu Tarbiyah Ibnu Sina Malang, 2022)
Learning Arabic in the new normal with the blended learning model can use media that can be accessed by the internet. One of the media that is easily accessible anytime and anywhere is Youtube. The purpose of this literature review is to describe the experience of educators in optimizing Arabic listening skills using Youtube media. The focused aspects are the steps of educators and evaluation of the use of YouTube as a medium to optimize Arabic listening skills. Educators need to adapt the themes, indicators, and learning objectives to the content. The recommendations for Youtube channels that can be used are Arabic Podcast, Dars Arobi, and Ammiko Az. The channel provides listening content ranging from simple dialogues to short animated films in Arabic. Its use requires synergy between educators, students and coordination with parents for online sessions from home. With the planning according to the needs of students, the implementation of conducive learning, and proper evaluation, students' listening skills can be optimized.